Analysis of Public Service Development Strategies of the Transportation Department of Kampar District - Tambunan, Agustinus; Arman, Arman; Yusup, Yusup (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to determine the most appropriate strategy for developing public services of the Department of Transportation of Kampar Regency. The sample of this study amounted to 10 people, including echelon III and echelon IV officials and functional officials of the Kampar Regency Transportation Office who have 5-10 years of experience and knowledge or more related to the Kampar Regency Transportation Office. Research data processing was carried out by SWOT Analysis (Strenght, Weakness, Opportunity, Threat), namely by analyzing internal factors (Internal Strategic Factors Analysis Summary / IFAS) and external factors (External Strategic Factors Analysis Summary / EFAS) of the Kampar Regency Transportation Office. The results showed that the strategic position map of the Kampar Regency Transportation Agency is in Quadrant I with a value of +0.89 on internal factors and a value of +0.50 on external factors, meaning that the agency can establish aggressive policies because it has great potential in improving public services by taking advantage of existing opportunities or by implementing the right strategy, namely using the SO strategy. These strategies include utilizing the right management and organizational structure to implement local government programs, coordinating well with ministries, provinces and other districts to improve Human Resources (HR), utilizing the development of Information Technology, especially in terms of public services to all existing departments and Technical Implementation Units (UPT), increasing the income of Regional Original Revenue (PAD) with the support of other stakeholders and utilizing the role of the private sector through Corporate Social Responsibility (CSR) funds to support public services to the wider community